Pelatihan Etika Bermedia Sosial Berbasis Nilai-Nilai Keislaman Bagi Remaja Desa Karang Kemiri Belitang - Akhsanul Huda; Syafrizal Fuady; Widodo Widodo (Institut Agama Islam Insan Prima Misbahul Ulum Gumawang, 2026)
The development of digital technology and social media exerts a major influence on adolescent behavior. On one hand, it provides easy access to information, but on the other hand, it causes negative impacts such as hoaxes, cyberbullying, hate speech, and low digital communication ethics. This condition also occurs in adolescents in Karang Kemiri Village, Belitang District, who are active on social media but lack an understanding of cyber ethics. This community service activity aims to increase adolescents' understanding and awareness of social media ethics based on Islamic values. The service partners in this activity are the local village youth community consisting of junior high, senior high school students, and youth organizations. The method used is participatory training which includes the stages of initial observation, program socialization, material delivery, case simulation, and evaluation-reflection procedures. The data were analyzed using qualitative descriptive techniques. The results show a significant increase in participants' understanding of digital ethics and a commitment to implementing Islamic values such as tabayyun, honesty, politeness, and responsibility in cyberspace. This activity is meaningful as a preventive step in shaping the character of village youth to be digitally smart and noble.